2014
DOI: 10.3747/pdi.2012.00190
|View full text |Cite
|
Sign up to set email alerts
|

Patient Education and Care for Peritoneal Dialysis Catheter Placement: A Quality Improvement Study

Abstract: ORIgINAL ARTICLES♦ Background and Objectives: Peritoneal dialysis catheter (PDC) complications are an important barrier to peritoneal dialysis (PD) utilization. Practice guidelines for PDC placement exist, but it is unknown if these recommendations are followed. We performed a quality improvement study to investigate this issue. ♦ Methods: A prospective observational study involving 46 new patients at a regional US PD center was performed in collaboration with a nephrology fellowship program. Patients complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The method of training is often believed to affect the risk of catheter-related infections (79,80). An observational study found that the rate of ESI was reduced 10-fold with a program that incorporated intensive training of nursing staff and patients, improved operative aseptic technique and reduction in S. aureus nasal carriage (81).…”
Section: Training Programsmentioning
confidence: 99%
“…The method of training is often believed to affect the risk of catheter-related infections (79,80). An observational study found that the rate of ESI was reduced 10-fold with a program that incorporated intensive training of nursing staff and patients, improved operative aseptic technique and reduction in S. aureus nasal carriage (81).…”
Section: Training Programsmentioning
confidence: 99%
“…31 Coordination of care also is challenged when PD nurses do not feel comfortable questioning operator practices. 31 To address these issues, the nephrologist must help educate the operator about best practices and ensure implementation of standardized care protocols. Such protocols should emphasize patient education and communication with dialysis caregivers.…”
Section: Operatormentioning
confidence: 99%
“…There should be a clear algorithm reflecting operator responsibilities and a periodic audit of quality metrics. 31 …”
Section: Operatormentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, those fellows will become the committed nephrologists who tackle the infrastructure barriers by promoting surgical and nursing expertise. This deficiency has been well documented (8,9) and recently re-emphasized (2,3). Competency in PD is determined at the local level by the training program director.…”
mentioning
confidence: 99%